Second generation HIV surveillance in Pakistan: policy challenges and opportunities - Munro, Michelle (BMJ Publishing Group, 2013)
From 2004 to 2011, the Canada-Pakistan HIV/AIDS Surveillance Project (HASP) worked with government and non-government partners in Pakistan to design and implement an HIV second generation surveillance (SGS) system. Insights into the development of scalable cost effective surveillance methodologies, implementation, use of data for HIV prevention and human rights were gained over the course of HASP. An ideal SGS system would be affordable, able to be implemented independently by local partners and produce data that could be readily applied in policy and programmes. Flexibility in design and implementation is important to ensure that any SGS system is responsive to information needs, political changes and changes in key population dynamics and HIV epidemics. HASP's mapping methodology is innovative and widely accepted as best practice, but sustainability of the SGS system it developed is a challenge.